Kinetics of Dehydration of Aroids and Developed Dehydrated Aroids Products - Kamruzzaman, M; Islam, MN (Journal of Chemical Engineering, 2010)
The study was concerned with the dehydration kinetics of aroids in mechanical dryer at different drying condition such as variable air dry bulb temperature and air velocity. Fresh aroids with 3, 5 mm slice and 8 mm cube were used as raw materials for drying. The experimental results showed that drying rate constant and thickness can be expressed as power law equation. The exponent of the equation for aroids was 1.15 indicating presence of significance external mass transfer resistance. Increasing loading density gave decreased drying rate constant and when air velocity of dryer was increased, drying rate constant was also increased, as higher air velocity reduces the external resistance to mass transfer and also higher temperature gave faster drying rate. The activation energy of diffusion of water from aroids during drying as per Arrhenius equation was found to be 5.12 k cal/g-mole. The chemical compositions of fresh and dried aroids were determined and it was observed that all the constituent remained almost constant, only fat decreased slightly possibly due to oxidation. Organoleptic taste testing showed that “chapatti” prepared from aroids powder (aroids powder: wheat flour = 1:4) were adjudged to be the best by the panelists using 1-9 hedonic scale and ranked as like moderately securing score 7.3. Journal of Chemical Engineering Vol.ChE 24 2006 19-24